Impact of Nonpharmaceutical Interventions on infectious disease patterns in Yunnan Province across COVID-19 pandemic phases - Chen, Lihua; Gao, Huxing; Zhang, Jiarui; Xu, Chuanzhi; Lu, Shuiping; Pan, Yue; Thilakavathy, Karuppiah; Zhao, Shiwen; Xiong, Chenglong; Sun, Zhong (BioMed Central, 2026)
Background: The COVID-19 pandemic substantially altered global infectious disease patterns. Nonpharmaceutical interventions (NPIs)—including lockdowns, travel restrictions, and enhanced hygiene—were widely implemented to control SARS-CoV-2 but also influenced the transmission of other infectious diseases. This study assessed the impact of NPIs on 36 notifiable diseases in Yunnan Province, China, across three phases: the prepandemic period (2014–2019), the pandemic phase (2020–2022), and the postpandemic phase (2023), when most NPIs were lifted. Methods: We analyzed surveillance data from the Yunnan Provincial CDC using Poisson regression, Spearman correlation, and bootstrap resampling. Incidence ratios and temporal trends were compared across phases, adjusting for population size. All analyses were performed using R. Results: During the pandemic phase, NPIs significantly suppressed several diseases, including leptospirosis (− 97.4%, P < 0.001), rabies (− 90.2%, P < 0.001), and schistosomiasis (− 88.9%, P < 0.05), likely due to reduced mobility and improved hygiene. In contrast, brucellosis (+ 195%, P < 0.001) and pertussis (+ 559.3%, P < 0.001) increased, potentially due to service disruptions. After NPI relaxation in 2023, marked rebounds were observed in dengue fever (+ 5027.4%, P < 0.001) and influenza (+ 1304.3%, P < 0.001), likely reflecting waning population immunity. However, sustained reductions persisted in tuberculosis (− 12.5%, P < 0.001) and rubella (− 89.3%, P < 0.001). Conclusions: NPIs, especially travel restrictions and improved hygiene, effectively curtailed the transmission of multiple infectious diseases in Yunnan during the pandemic phase. The postpandemic resurgence of several diseases underscores the importance of sustained surveillance and context-tailored public health strategies to maintain disease control and strengthen system resilience.